Remembering through walls: public memory, counter-visuality, and postcolonial narratives in Indonesian commemorative murals - Winie Setia Prilapnita Hapsari (Indonesian Journal of Language, Space, and Visual Arts, 2026)
Background: Indonesian commemorative murals have become contested public surfaces through which heroic nationalism, traumatic remembrance, local history, and unresolved demands for accountability are made visible. Objective: This study examines how commemorative murals construct public memory, redistribute visibility, and position postcolonial narratives between completed liberation and unfinished citizenship. Method: Using a qualitative comparative design, this study analyses sixteen primary mural items documented across eight Indonesian provinces between 2014 and 2024, supported by five scholarly sources and four contextual documents, through a Public Memory–Spatial Salience Matrix, a Counter-Visuality and Visibility Contestation Grid, and a Postcolonial Narrative Positioning Framework. Results: Findings show that official-national and community-national murals dominate mnemonic representation by translating founders, heroes, and independence struggles into civic pedagogy. Activist and traumatic murals instead mobilise accusation, mourning, victim naming, and evidentiary display to reopen unresolved political violence and institutional accountability. Implication: Vernacular and local-historical murals pluralise national memory through maritime histories, kampung authorship, and indigenous visual grammars, although some remain incorporated into heritage branding. Novelty: This study introduces an integrated analytical model that treats commemorative murals simultaneously as visual compositions, spatial memory infrastructures, and postcolonial narrative interventions, thereby clarifying how mnemonic authority, representational inequality, and public visibility intersect within Indonesian urban culture across diverse institutional and community settings.